Antiproliferative effects of mealworm larvae (Tenebrio molitor) aqueous extract on human colorectal adenocarcinoma (Caco‐2) and hepatocellular carcinoma (HepG2) cancer cell lines. Issue 7 (1st June 2021) - Ding, Qingzhi; Wu, Ricardo A.; Shi, Tingting; Yu, Yanhua; Yan, Yilin; Sun, Nianzhen; Sheikh, Arooj Rehman; Luo, Lin; He, Ronghai; Ma, Haile
Abstract: Recently, insects have aroused the interest of researchers as potential therapeutic resources against malignant diseases such as cancer. In this study, the effects of aqueous extracts from mysore thorn borer (MTB) ( Anoplophora chinensis ) and mealworm larvae (MWL) ( Tenebrio molitor ) against cancer cells were investigated. MWL aqueous extract showed higher antiproliferative effects against Caco‐2 and HepG2 cells compared to MTB. The IC50 (48 hr) of MWL aqueous extract were 11.44 and 20 mg/ml for Caco‐2 and HepG2 respectively. Flow cytometry analysis showed that MWL aqueous extract induced apoptosis in Caco‐2 and HepG2 increasing from 2.06% to 74.34% and from 0.04% to 42.14% after 24 hr respectively. Caspase activity assay showed that apoptosis was mediated via death receptor pathway mediated by caspase‐8 and ‐9 followed by the activation of caspase‐3; caspase‐3 may have induced DNA damage and cell death. These effects may be correlated to its free amino acids. The results of this study demonstrate the potentials of MWL in the development of natural anticancer therapeutics in the future. Practical applications: Natural nutraceuticals from insects might be useful for the treatment and prevention of cancers such as colorectal and liver cancer. In recent years, edible insects have caught the attention of researchers, because of their potential as an alternative source of food and nutraceuticals. The results of our study showed that MWL extract might provide important anticancer compounds against colon and liver cancer. Abstract : Mealworm larvae ( Tenebrio molitor ) (MWL) aqueous extract showed antiproliferative effects against Caco‐2 and HepG2 cells. The IC50 (48 hr) of MWL aqueous extract were 11.44 and 20 mg/ml for Caco‐2 and HepG2 respectively. MWL aqueous extract induced apoptosis in Caco‐2 and HepG2 increasing from 2.06 to 74.34% and from 0.04 to 42.14% after 24 hr respectively. Apoptosis was mediated via death receptor pathway mediated by caspase ‐8 and ‐9 followed by the activation of caspase‐3.